2019
DOI: 10.3389/fgene.2019.00133
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifications in Acute Myeloid Leukemia: Prognosis, Treatment, and Heterogeneity

Abstract: Leukemia, specifically acute myeloid leukemia (AML), is a common malignancy that can be differentiated into multiple subtypes based on leukemogenic history and etiology. Although genetic aberrations, particularly cytogenetic abnormalities and mutations in known oncogenes, play an integral role in AML development, epigenetic processes have been shown as a significant and sometimes independent dynamic in AML pathophysiology. Here, we summarize how tumors evolve and describe AML through an epigenetic lens, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 182 publications
(242 reference statements)
0
50
0
1
Order By: Relevance
“…AML is complex disease with a diverse genetic landscape. Recent studies have revealed that epigenetic dysregulation plays an important role in leukaemia pathogenesis [6,11]. Further histone-modifying enzymes reportedly contribute to leukaemia pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…AML is complex disease with a diverse genetic landscape. Recent studies have revealed that epigenetic dysregulation plays an important role in leukaemia pathogenesis [6,11]. Further histone-modifying enzymes reportedly contribute to leukaemia pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from The Cancer Genome Atlas Network (2013), the count of genomic mutations tends to be less in AML than in other cancers (33). Moreover, a similar distribution of mutations was observed before and after progression, but methylation pro le shifts and have a functional impact on gene regulation(34), suggesting the increasing signi cance of understanding epigenetic changes in AML.…”
Section: Discussionmentioning
confidence: 99%
“…AML is a very heterogeneous disease and this heterogeneity has been demonstrated both by cytogenetic and molecular genetic analyses as well as gene expression, epigenetic, and possibly also proteomic and metabolic profiling [ 12 , 43 , 44 , 45 , 46 , 47 , 48 ]. The most important factors for evaluation of AML relapse risk in routine clinical practice are the cytogenetic and the molecular genetic abnormalities (these and other prognostic factors are gathered in Table 1 ).…”
Section: Aml Heterogeneity and Prognostic Evaluationmentioning
confidence: 99%